A fundamental study for predicting the urban street noise by use of the image method approach - OHTA, Mitsuo; MITANI, Yasuo (Archives of Acoustics, 1985)
This paper describes a unified statistical method of structural prediction of an arbitrarily fluctuating street noise in the general urban noise environment, especially from a fundamental viewpoint. That is, an analytical expression of the noise propagation characteristics for several cases of typically idealized road traffic models is first derived, in order to express an actual noise environment in the city area, based on the image method approach. Then, by using the newly derived expression of the noise propagation characteristics, two representative evaluation indices of street noise, closely related to the well-known L_eq and L_NP evaluation indices, can be given in an explicit functional form with several internal mechanisms of the road traffic environments in the city area. Finally the validity of the present theoretical prediction method is experimentally confirmed, especially by use of digital simulation technique for several cases of typically idealized actual road traffic noise environment in the city area.